2020
DOI: 10.1111/cdev.13385
|View full text |Cite
|
Sign up to set email alerts
|

Teaching With Televised Stories: A Story‐Focused Narrative Preview Supports Learning in Young Children

Abstract: Researchers examined the effects of previewing on preschoolers’ comprehension of narrative and educational content in a television program. Children (3–5 years, N = 107) watched an educational math episode in one of three conditions: no‐preview control, education‐focused expository preview, or story‐focused narrative preview. A main effect of previewing was found, controlling for age, character familiarity, prior knowledge, and visual attention. Specifically, the narrative preview enhanced both narrative compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 62 publications
3
14
0
Order By: Relevance
“…When analysing 5‐year‐olds separately, a concurrent significant negative association exists between vocabulary and screen media. This model validates earlier cross‐sectional research which suggests that early screen time is associated with poorer vocabulary growth 8,9 . Our findings reinforce and build upon the outcomes of an earlier longitudinal study which showed the impact of screen time at 1 year of age on subsequent communication skills at 2 and 4 years of age 28…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…When analysing 5‐year‐olds separately, a concurrent significant negative association exists between vocabulary and screen media. This model validates earlier cross‐sectional research which suggests that early screen time is associated with poorer vocabulary growth 8,9 . Our findings reinforce and build upon the outcomes of an earlier longitudinal study which showed the impact of screen time at 1 year of age on subsequent communication skills at 2 and 4 years of age 28…”
Section: Discussionsupporting
confidence: 89%
“…High levels of screen media exposure have been negatively associated with learning, language, self‐regulation and early parent–child interaction 3–6 . Conversely, screen media have also been shown to provide the child with new ideas and provide opportunities for early learning and literacy development 3,7,8 . A meta‐analysis has demonstrated the negative association screen media has with language development, 9 although another meta‐analysis nuances the relationship and shows positive correlations with foremost laboratory‐based word learning from screens 8 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there was variation in the types of supports featured by program and language. Despite these differences, researchers continue to investigate the specific mechanisms on screen that promote vocabulary learning from screens (Jing & Kirkorian, 2020; Linebarger & Piotrowski, 2010).…”
Section: Vocabulary Learning From Educational Mediamentioning
confidence: 99%
“…Some skills such as thinking systematically, empathizing, learning more effectively and permanently can be acquired to the students with the genre of story (Oller, 1983:49). The story is ideal for children and even adults to understand and describe the world (Freeman et al, 2011:2;Gudmundsdottir, 1991:207;Jing andKirkorian, 2020:1101;McKeough et al, 2005:242). In order to be a good storywriter, systematic thinking skills, physical maturity, and psychological competence to recognize the target audience are required (Filipi, 2017:279).…”
Section: Introductionmentioning
confidence: 99%